Жизни трепетная нить: стихи / Надежда Тронина ; [редактор- составитель А. А. Гребенкин] - Тронина Надежда Николаевна (МиГ, 2005)
Экземпляры: ф.2 (2006) / Инвентарный номер: 49778 / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: Т 73 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5